The Metabolic Syndrome Is Associated With Lower Cognitive Performance and Reduced White Matter Integrity in Midlife: The CARDIA Study - Dintica, Christina S.; Hoang, Tina; Allen, Norrina; Sidney, Stephen; Yaffe, Kristine (Frontiers in Neuroscience, 2022)
Background: Cardiovascular disease risk factors play a critical role in brain aging. The metabolic syndrome (MetS), a constellation of cardiovascular risk factors, has been associated with poorer cognition in old age, however it is less clear if it is connected to brain health earlier in life. Methods: We investigated the association of MetS (n=534, 18.5%) vs no MetS (n= 2346, 81.5%) and cognition in midlife within the prospective study, Coronary Artery Risk Development in Young Adults (CARDIA). At midlife (mean age 50), MetS was defined using National Cholesterol Education Program guidelines. At the 5-year follow-up, a cognitive battery was administered including tests of processing speed (Digit Symbol Substitution Test, DSST), executive function (the Stroop Test), verbal memory (Rey Auditory Verbal Learning Test, RAVLT), Verbal Fluency (category and letter fluency), and global cognitive function (Montreal Cognitive Assessment, MoCA). A sub-sample (n= 453) underwent brain MRI. Results: Participants with MetS had worse performance on tests of verbal fluency, processing speed, executive function, and verbal memory (p<0.05), but not on global cognition. MetS was also associated with lower frontal, parietal, temporal and total white matter integrity (p<0.05), as assessed with fractional anisotropy. Conclusions: MetS is associated with lower cognition and microstructural brain alterations already at midlife, suggesting that MetS should be targeted earlier in life in order to prevent adverse brain and cognitive outcomes.